The woodsman - Kassell, Nicole; Bacon, Kevin; Sedgwick, Kyra; Eve (Musician); Sundance Channel (Culver City, CA : Sony Pictures Home Entertainment, 2005)
Released from prison after twelve years a pedophile returns to his hometown. As he begins to start a new life his past continually haunts him.
Originally released as a motion picture in 2004
Features: Sundance Channel featurette, director commentary, previews.
Kevin Bacon, Kyra Sedgwick, Eve.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
In English with optional English or French subtitles.
Keywords: Child molesters -- Drama; Sex offenders -- Drama; Ex-convicts -- Drama; Video recordings for hard of hearing people; Feature films